2012
DOI: 10.1103/physrevlett.109.246601
|View full text |Cite
|
Sign up to set email alerts
|

Spin-Valve-Like Magnetoresistance inMn2NiGaat Room Temperature

Abstract: Spin valves have revolutionized the field of magnetic recording and memory devices. Spin valves are generally realized in thin film heterostructures, where two ferromagnetic (FM) layers are separated by a nonmagnetic conducting layer. Here, we demonstrate spin-valve-like magnetoresistance at room temperature in a bulk ferrimagnetic material that exhibits a magnetic shape memory effect. The origin of this unexpected behavior in Mn(2)NiGa has been investigated by neutron diffraction, magnetization, and ab initio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
52
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(59 citation statements)
references
References 27 publications
4
52
0
3
Order By: Relevance
“…4f shows an interesting behavior, an asymmetric MR around H = 0, which is similar to that observed in spin-valve-like MR effect in other systems, e.g. Mn 2 NiGa [25], where the mechanism was explained by antisite disorder, in which Ga atom sites are partially occupied by Mn atoms forming FM nanoclusters coupled antiparallel to the other Mn atoms. The observed negative but asymmetrical MR in low magnetic field shown in Fig.…”
Section: K Respectively As Shown Insupporting
confidence: 60%
“…4f shows an interesting behavior, an asymmetric MR around H = 0, which is similar to that observed in spin-valve-like MR effect in other systems, e.g. Mn 2 NiGa [25], where the mechanism was explained by antisite disorder, in which Ga atom sites are partially occupied by Mn atoms forming FM nanoclusters coupled antiparallel to the other Mn atoms. The observed negative but asymmetrical MR in low magnetic field shown in Fig.…”
Section: K Respectively As Shown Insupporting
confidence: 60%
“…The M(T ) plot in a low applied magnetic field of 50 Oe for annealed bulk samples shown in Fig. 5(a) reveals M s , M f , A s , and A f for Mn 1.75 Ni 1.25 Ga as 139, 134, 160, and 175 K, respectively, whereas the corresponding temperatures for Mn 1.9 Ni 1.1 Ga are 264, 160, 230, and 315 K. The drop at M s is related to the large magnetocrystalline anisotropy and lower magnetization of the martensite phase in these MSMAs [10,18,24]. A comparison of x-ray powder-diffraction profiles of the as-ground powder samples and the same powder after it was annealed at 773 K for 10 h (Fig.…”
mentioning
confidence: 99%
“…The austenite phase of Mn excess Ni-Mn-In alloys is known to be ferromagnetic whereas the martensite phase is generally believed to be nonmagnetic (either paramagnetic or antiferromagnetic) [6,8,11], whereas in the Mn excess Ni-Mn-Ga alloys, both the austenite and the martensite phases are reported to be ferrimagnetic [10,[16][17][18]. Using high-resolution synchrotron and laboratory x-ray powder-diffraction (XRD) data, it is shown that the martensite structure can be stabilized by residual stresses over a wide temperature range well above A f in both alloy systems.…”
mentioning
confidence: 99%
“…A different mechanism was responsible for the spin-valve-like MR observed in bulk Mn 2 NiGa Heusler alloys; this was explained as a result of antisite coupling of Mn atoms located in the Ga positions, forming ferromagnetic nanoclusters coupled antiferromagnetically to the other Mn atoms [8].…”
Section: Introductionmentioning
confidence: 99%